SEASONAL DISTRIBUTION OF MICROBIAL BIOMASS CARBON AND SOME HEAVY METALS AROUND THE INDUSTRIAL AREA OF KANO METROPOLIS, NORTHWESTERN-NIGERIA - Mohammed, Mansur Abdul; Buba, Luka Fitto (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2020)
The accumulation of toxic heavy metals in excessive quantities has a detrimental effect on soil quality which interferes with key biochemical processes in soils. It is very imperative to explore soil microbial activities concerning to environmental conditions for sustainable soil management. The study aimed to assess the seasonal distribution of soil microbial biomass carbon (MBC), some heavy metals and pH, and their relationship in the soil ecosystem. Field investigation and laboratory analysis were the main methods adopted as sources of generating data and analyses. Ten soil samples were collected using composite sampling techniques on seasonal bases and then analyzed in the laboratory. The results were subjected to statistical analyses using t-test and the Analysis of Variance (ANOVA) at <0.05. Pearson’s correlation andregression analysis was analyzed to determine the relationship among the variable at P<0.05. The results show that locations with higher values of MBC corresponded with locations with high Cr, Cd, and Pb. High values of Cr, Cd, and Pb were observed in the dry season. On the other hand, in the wet season, rainfall enthused dilution, leaching, and runoff of Cr, Cd, and Pb and then removed from subsurface. High MBC in the wet season is due to favorable conditions for the microbial population and rapid mineralization due to high moisture and temperature than the dry season where there are low moisture and temperature. The analysis revealed that MBC was positively related to Cr, Pb, and was negatively related to Cd. However, the variation of MBC was explained by Cr, Cd, and Pb by 64% and 52% for dry and wet season respectively. It was concluded that the toxicity of heavy metals in soil depends on the pH level and therefore, determination of MBC, Cr, Cd, Pb, pH, and temperature of soil reflect the microbial activities in the soil and could be considered as soil quality indicators.